2020
DOI: 10.1097/gme.0000000000001498
|View full text |Cite
|
Sign up to set email alerts
|

Differences between accelerometer cut point methods among midlife women with cardiovascular risk markers

Abstract: Objective: Midlife women experience elevated risk for cardiovascular disease and often receive advice to increase physical activity to mitigate this risk. Use of accelerometers to measure ambulatory physical activity requires selection of appropriate thresholds for estimating moderate-to-vigorous physical activity (MVPA), and choice of cut points may lead to meaningfully different conclusions about midlife women's physical activity (PA) engagement. This is particularly important given the recent el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…Total minutes in MVPA vs. bouted MVPA At 5 years after surgery, 72.2% of participants met current MVPA recommendations (≥150 MVPA minutes/week) based on total minutes in MVPA but only 16.5% of participants met previous MVPA recommendations based on bouted MVPA minutes. These data are aligned with findings within the general adult population [37][38][39], but represent novel information on the bariatric surgery population. Choosing the one method over the other clearly decides if our participants are described as a highrisk group for chronic diseases or not, and whether their PA level compares to, or exceeds, the PA level of the general adult population.…”
Section: Association With Weight Recurrencesupporting
confidence: 77%
See 1 more Smart Citation
“…Total minutes in MVPA vs. bouted MVPA At 5 years after surgery, 72.2% of participants met current MVPA recommendations (≥150 MVPA minutes/week) based on total minutes in MVPA but only 16.5% of participants met previous MVPA recommendations based on bouted MVPA minutes. These data are aligned with findings within the general adult population [37][38][39], but represent novel information on the bariatric surgery population. Choosing the one method over the other clearly decides if our participants are described as a highrisk group for chronic diseases or not, and whether their PA level compares to, or exceeds, the PA level of the general adult population.…”
Section: Association With Weight Recurrencesupporting
confidence: 77%
“…Also, only evaluating bouted minutes in MVPA might exclude many individuals within the bariatric surgery population because many do not engage in prolonged bouts of MVPA [27]. Importantly, studies within the general population find that using total minutes or bouted minutes in MVPA influence how participants are categorized [37][38][39]. Similar data is not available within the postbariatric surgery population.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, BCTs and intervention features that were described as activating BCTs were extracted. An initial set of BCTs were selected for extraction based on the authors' familiarity with physical activity intervention research (specific to women in midlife and more broadly; Arigo, 2015 ; Butryn et al, 2016 ; Arigo et al, 2020a , b ). These BCTs included the following [with Michie et al ( 2013 ) associated numeric codes]: goal setting (proximal behavior [1.1] and/or distal outcome [1.3]), self-monitoring (proximal behavior [2.3] and/or distal outcome [2.4]), providing feedback (2.2), problem-solving and/or planning (1.4 and 1.2, respectively), social support (3.1–3.3), social comparison (6.2), and behavioral modeling (6.1).…”
Section: Methodsmentioning
confidence: 99%
“…Individuals are excluded from participation if they do not meet the above criteria or if they state an intention to move away from the geographic area during the study period. Eligibility was not limited by current level of PA engagement, as existing evidence and pilot work suggested that engagement would range from low to moderate for the target population [ 115 , 116 ].…”
Section: Methodsmentioning
confidence: 99%